Situation Report: Hungary, 22 May 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Characteristic Features of Hungarian-Soviet Economic Relations Hungarian-Yugoslav Economic Co-operation Talks Hungary's Medicinal Spas: A Natural Tourist Attraction New Schedule for Radio Budapest's Foreign Service Successful Adoption of Closed Production System in Crop Growing Agricultural Relations between Hungary and the West